Relationship of emotional intelligence level and coping strategies investigation (The Journal of Psychology and Sociology, 2019)
The question of the psychological health of the individual is key in the process of his life. Inside this phenomenon, a huge place is occupied by emotional intelligence, as a complex element that influences both the somatic and the mental state of a person. The growing interest in the subject of emotional intelligence demonstrates the importance of this competence for a person in the 21st century, in his professional activities. In this paper, emotional intelligence is one of the key elements of professional health. The ability to identify, understand, manage your emotions and the emotions of others contributes to effective interaction in the work system, in our case, the doctorpatient system. An adult spends most of his time at work and his general health correlates with the emotional background in the workplace, satisfaction with his work and the effectiveness of communication. The working environment, for an adult person is the main source of stress and tension, which affects its overall productivity, as a unit of labor. Work on the emotional competence of professional doctors, will allow not only to establish local work of medical services, but also increase the overall health index in the country.Key words: emotional intelligence, coping strategies, professional health, doctors.